2016
DOI: 10.1021/acssynbio.6b00180
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and Function of a Plant Chromosome in Human Cells

Abstract: Replication, segregation, gene expression, and inheritance are essential features of all eukaryotic chromosomes. To delineate the extent of conservation of chromosome functions between humans and plants during evolutionary history, we have generated the first human cell line containing an Arabidopsis chromosome. The Arabidopsis chromosome was mitotically stable in hybrid cells following cell division, and initially existed as a translocated chromosome. During culture, the translocated chromosomes then converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…There are very few examples in eukaryotes of foreign DNA recruiting host CENH3 to maintain a chromosome. Human centromeres have previously been shown to function in mouse chromosomes (58), and in a recent example, Arabidopsis centromeric repeats were shown to recruit human CENH3 and maintain chromosomes in human cells (59). In both cases, the chromosomes maintained by foreign DNA originally derived from chimeric host-donor DNA chromosomes followed by chromosomal breakage and/or rearrangement, resulting in smaller linear chromosomes or "mini-chromosomes."…”
Section: Discussionmentioning
confidence: 99%
“…There are very few examples in eukaryotes of foreign DNA recruiting host CENH3 to maintain a chromosome. Human centromeres have previously been shown to function in mouse chromosomes (58), and in a recent example, Arabidopsis centromeric repeats were shown to recruit human CENH3 and maintain chromosomes in human cells (59). In both cases, the chromosomes maintained by foreign DNA originally derived from chimeric host-donor DNA chromosomes followed by chromosomal breakage and/or rearrangement, resulting in smaller linear chromosomes or "mini-chromosomes."…”
Section: Discussionmentioning
confidence: 99%
“…Artificial cell fusions can be induced by Sendai virus (Okada 1962), polyethylene glycol (PEG) (Pontecorvo 1976), or electroporation (Zimmermann & Scheurich 1981). The latest study reported human-plant hybrid cells maintaining chromosomes from both species (Wada et al 2016), indicating that xenogenic cell fusion is a powerful method to provide useful biological tools. The latest study reported human-plant hybrid cells maintaining chromosomes from both species (Wada et al 2016), indicating that xenogenic cell fusion is a powerful method to provide useful biological tools.…”
Section: Introductionmentioning
confidence: 99%
“…Using these techniques, various xenogenic hybrid cells and organisms have been developed, for example pomato (Melchers et al 1978). The latest study reported human-plant hybrid cells maintaining chromosomes from both species (Wada et al 2016), indicating that xenogenic cell fusion is a powerful method to provide useful biological tools. However, for economic mass-production of the hybrids, current fusogenic approaches are not convenient, efficient or scalable.…”
Section: Introductionmentioning
confidence: 99%
“…However, the first plant-animal hybrid cells survived only 6 days. Recently, human and Arabidopsis hybrid cells were generated by PEG cell fusion (Wada et al 2017).…”
mentioning
confidence: 99%
“…Thus, a synthetic genome should include both nuclear and plastid genomes with an efficient design to reduce functional redundancy compared with the animal genome. Such a down-sized genome design should be possible because mRNAs from plant genes integrated into the human genome were detected in human cells, suggesting that plant genes can be transcribed using the human transcription system (Wada et al 2017). Molecular analyses of planimal cells using transcriptomic, proteomic, metabolomic and epigenetic analyses will give us new insights into the universality and specificity of molecular mechanisms between plants and animals.…”
mentioning
confidence: 99%